PU.1 Is Required for the Developmental Progression of Multipotent Progenitors to Common Lymphoid Progenitors - Pang, Swee Heng Milon; de Graaf, Carolyn A.; Hilton, Douglas J.; Huntington, Nicholas D.; Carotta, Sebastian; Wu, Li; Nutt, Stephen L. (Frontiers in Immunology, 2018)
The transcription factor PU.1 is required for the development of mature myeloid and lymphoid cells. Due to this essential role and the importance of PU.1 in regulating several signature markers of lymphoid progenitors, its precise function in early lymphopoiesis has been difficult to define. Here, we demonstrate that PU.1 was required for efficient generation of lymphoid-primed multipotent progenitors (LMPPs) from hematopoietic stem cells and was essential for the subsequent formation of common lymphoid progenitors (CLPs). By contrast, further differentiation into the B-cell lineage was independent of PU.1. Examination of the transcriptional changes in conditional progenitors revealed that PU.1 activates lymphoid genes in LMPPs, while repressing genes normally expressed in neutrophils. These data identify PU.1 as a critical regulator of lymphoid priming and the transition between LMPPs and CLPs.